Optimization of borehole diameter to improve rock fragmentation in open-pit limestone mine bench blasting - Haiwang Ye; Menghao Yu; Binhong Shi; Yan Yu; Fengchuan Shang; Yefeng Dong; Tao Lei; Ning Li; Qizhou Wang (Scientific Reports)
Abstract Blasting fragmentation distribution in open-pit mines directly affects the efficiency and cost of subsequent production, so controlling the reasonable distribution of rock blasting fragmentation is one of the main objectives of surface mine bench blasting. Taking a limestone mine as an example, numerical simulation tests and field bench blasting tests with different borehole diameters were conducted to optimize the rock blasting fragmentation distribution. The results of numerical simulation indicate that there is an exponential functional relationship between the cumulative volume proportion of the limestone blasting fragments and dynamic damage value of the numerical model. When the borehole diameter changes from 90 to 190 mm and the powder factor remains constant, there is a cubic functional relationship between the average fragmentation size of rock blasting and the borehole diameter, and quadratic functional relationships between the big block rate, powder ore rate, and the borehole diameter, respectively. The attenuation rate of explosive stress waves during blasting with larger borehole diameters is faster than that with smaller borehole diameters. A borehole diameter of 115 mm yields the most significant stress superposition effect in the inter-borehole region. The results of field bench blasting tests show that compared to the 140 mm borehole diameter, the 115 mm borehole diameter blasting can decrease the proportion of fragments larger than 900 mm and powder ore (0–5 mm) by 52.91% and 33.85%, respectively, and increase the proportion of fragments sized 20–40 mm by 71.40%.